Morality : an anthropological perspective - Zigon, Jarrett (Oxford ; New York : Berg, 2008)
Zigon here provides an account of anthropological approaches to the question of morality. By considering how morality is viewed and enacted in different cultures, and how it is related to key social institutions, he takes a closer look at some of the most central questions in the morality debates of our time.
Part I. The philosophical and theoretical foundations of social scientific studies of morality -- Part II. Religion and law -- Case study 1 : moral torment in Papua New Guinea -- Part III. Sexuality, gender, and health -- Case study 2 : morality and women's health in Post-Soviet Russia -- Part IV. Language, narrative, and discourse -- Case study 3 : narratives of moral experience in Moscow -- Part V. Closing.
Includes bibliographical references (p. 167-178) and index.
Keywords: Ethics -- Cross-cultural studies; Anthropology -- Psychology; Anthropological ethics